Cyber risk, intellectual property theft and cyberwarfare : Asia, Europe and the USA - Taplin, Ruth (Routledge studies in the growth economies of Asia, 2021)
"The desire to steal the Intellectual Property (IP) of others be they creative individuals or the fruits of company teams working in patent pools to create new innovations remains the same. Political methods have become more sophisticated in terms of devaluing the output of creative humans by creating open source access which can be taken freely by all and sundry. What has changed is the new cyber based technology that allows increased theft of IP. Likewise, warfare for geo-political imperatives is not new but sophisticated cyber-based methods which can actually carry out infrastructural damage through cyberspace is new and accordingly termed cyberwarfare. How cyber strategies are used in IP theft and cyberwarfare in relation to new complex digital technology such as the Internet of Things is explored and in relation to particular essential sectors in the economy, marine, smart energy power grids and insurance. Country specific studies based on either being the recipient or perpetrator or both of cyberattacks are analysed in relation to Japan, China and North Korea, Russia, Europe (UK in particular), Iran and the USA"--